Chronic Disseminated Histoplasmosis in an Immunocompetent Man Presented as Bilateral Adrenal Masses with Partial Adrenocortical Insufficiency- A Rare Condition (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available   DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11371   J Bangladesh Coll Phys Surg 2012; 30: 58-59